SEBUAH INOVASI EDUPRENEURSHIP: IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS BALOK HIJAIYAH di TPQ SABDA DUA PEKALONGAN - Afroh Rozana; Kistanti Kistanti; Muhammad Tsaqolain Jaros; Muhammad Fajrul Falah; Wisnu Adji Yusuf Syahputra; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This qualitative case study investigates the innovation of the Hijaiyah Letter Blocks as an edupreneurial product at TPQ Sabda Dua Pekalongan, aiming to address fundamental challenges in Arabic language learning—namely students’ low motivation and limited mastery of the Hijaiyah alphabet. The study implements this game-based, hands-on learning medium and analyzes its effectiveness through data triangulation involving participant observation, in-depth interviews with instructors, and document analysis. Findings show that the kinesthetic and visual approaches enabled by the blocks significantly create an enjoyable learning experience while reducing student anxiety, with the medium’s uniqueness lying in its ability to transform passive learning into active, participatory engagement. Consequently, there is a clear improvement in classroom enthusiasm, speed in recognizing letter forms, and accuracy in assembling letters into syllables. From an edupreneurship perspective, the medium is not only pedagogically effective but also demonstrates commercial potential that can support institutional sustainability, with its economic value strengthening its position as a breakthrough in pioneering a sustainable educational business model. The study recommends further development in design aesthetics, game variations, and digital integration to expand its impact and appeal.